ANALYSIS OF CORPORATE REPUTATION BUILDING THROUGH CORPORATE STORY STRATEGY: (CASE STUDY ON GO-JEK ONLINE-BASED TRANSPORTATION SERVICE) - Fevrieranty, Wiisti Fenty (School of Communication - Atma Jaya Catholic University of Indonesia, 2018)
Reputation is important to strengthen the attractiveness of a company. Company with a positive reputation can more easily attract the target market by showing the uniqueness of the company as a competitive advantage. Nowadays, more and more companies are trying to build a positive reputation in order to maintain its success for long term. The purpose of this study is to analyze how the reputation building at Gojek as one of the technology-based companies through corporate story strategy that followed. This study uses qualitative research method by conducting content analysis techniques and in-depth interviews to many customers as their stakeholders. Content analysis was carried out on the content of www.go-jek.com site and the results showed that activity is a key element and is most strongly represented the corporate story in their official website. By implementing this corporate story strategy, Gojek can build a reputation platform by presenting elements of